Case report: One child with an autism spectrum disorder who had chronically elevated serum levels of CK and CK-MB - Rong, Ping; Zhao, Shuyi; Fu, Qianfang; Chen, Mengrui; Yang, Libin; Song, Yifei; Zhang, Xilian; Ma, Rong (Frontiers in Psychiatry, 2022)
Some patients with autism spectrum disorder have elevated serum creatine kinase levels, which are believed to associated with mitochondrial dysfunction. Although a few articles have reported this situation in the past, the increase is usually from 100 to 300 U/L, and there have been hardly any discussions on serum creatine kinase MB isoenzyme. This article discusses a 5-year-old child suffering from autism spectrum disorder, whose serum creatine kinase and creatine kinase MB isoenzyme have been rising for nearly two years, fluctuating at 584- 993U/L and 111- 625U/L respectively. Expect from behavioral and language symptoms associated with autism spectrum disorder, the child appears normal in other aspects. The child was prescribed with a traditional Chinese medicine decoction orally during the process and the serum creatine kinase MB isoenzyme level decreased dramatically to 111 U/L after the treatment. The present study is the first to record serum creatine kinase levels and the MB isoenzyme in patients with autism spectrum disorder for nearly two years, drawing the attention of clinicians to such situations, and a larger sample size and a longer study are necessary in the future.